Antihyperuricemic Activity of Tahongai (Kleinhovia hospita L.) Leaf Infusion in Mice (Mus musculus L.) - Sianturi, Sister; Sinaga, Clara Ritwany; Leswana, Nurillahi Febria; Butar-Butar, Maria Elvina Tresia; Simanullang, Raymon (Universitas Ahmad Dahlan, 2025)
Tahongai (Kleinhovia hospita L.) is recognized as a traditional medicinal plant originating from East Kalimantan. This species possesses various bioactive properties that contribute to health benefits, particularly from its leaves, which contain active compounds such as flavonoids, alkaloids, saponins, and terpenoids. These bioactive constituents have been reported to exhibit anti-hyperuricemic properties. This study aimed to evaluate the anti-hyperuricemic activity of K. hospita leaf infusion in hyperuricemic mice (Mus musculus L.), which were induced using chicken liver juice. The test material used was an infusion prepared from K. hospita leaves. The experimental design consisted of five treatment groups: a positive control group receiving allopurinol, a negative control group receiving distilled water, and three treatment groups administered K. hospita leaf infusion at varying concentrations of P1=15%, P2=30%, and P3=60%. The results indicated that the highest mean reduction in uric acid levels was observed in the P2 group, which received a 30% concentration of K. hospita leaf infusion, with an average percentage decrease of 19.12%. However, statistical analysis using One-Way ANOVA revealed a p-value greater than 0.05, indicating that there was no significant difference in uric acid reduction among the treatment groups.